The mental health of older adults in the criminal justice system: a brief report from a nominal group - Mulligan, Lee (The journal of forensic psychiatry & psychology, 2025)
The number of older people in prison is increasing, and this group has significant mental health needs. Despite this, little research has evaluated mental healthcare for older prisoners, and examples of best practice are unknown. This paper explored staff experiences of supporting the mental health needs of older prisoners to identify existing forms of care provision, challenges to implementation, and areas for improvement. Eight professionals were recruited to a nominal group discussion, and seven themes were identified: 1) Lack of recognition of mental health problems in prison; 2) Risk factors for mental health problems among older prisoners; 3) Models of working; 4) Specialised environments; 5) Prison transfers; 6) Aftercare post release; and 7) Mental health education. There was consensus that older prisoners are vulnerable to mental health problems, though their needs are not sufficiently recognised nor addressed. While several ideas for improvement were identified, the provision of consistent and effective mental health care for older prisoners is lacking. To identify best practice guidelines for addressing the mental health needs of older prisoners, a valuable next step is to review mental healthcare provision for older people in the community and consider how this could be adapted to a prison environment.